Dual-mode hydrophilic interaction normal phase and reversed phase liquid chromatography of polar compounds on a single column - Jandera, Pavel; Hájek, Tomáš (Wiley-VCH, 2020)
Adopting a stationary phase convention circumvents problematic definition of the boundary between the stationary and the mobile phase in the liquid chromatography, resulting in thermodynamically consistent and reproducible chromatographic data. Three stationary phase definition conventions provide different retention data, but equal selectivity: (i) the complete solid phase moiety; (ii) the solid porous part carrying the active interaction centers; (iii) the volume of the inner column pores. The selective uptake of water from the bulk aqueous-organic mobile phase significantly affects the volume and the properties of polar stationary phases. Some polar stationary phases provide dual-mode retention mechanism in aqueous-organic mobile phases, reversed-phase in the water-rich range, and normal-phase at high concentrations of the organic solvent in water. The linear solvation energy relationship model characterizes the structural contributions of the non-selective and selective polar interactions both in the water-rich and organic solvent-rich mobile phases. The inner-pore convention provides a single hold-up volume value for the retention prediction on the dual-mode columns over the full mobile phase range. Using the dual-mode monolithic polymethacrylate zwitterionic micro-columns alternatively in each mode in the first dimension of two-dimensional liquid chromatography, in combination with a short reversed-phase column in the second dimension, provides enhanced sample information.
Duální retenční mechanismus normální fáze – reverzní fáze na jedné LC chromatografické koloně pro polární látky
Keywords: dual retention mechanism; hydrophilic interaction liquid chromatography; mixed-mode columns; phase volume convention; two-dimensional separation; duální retenční mechanismus; chromatografie hydrofilních interakcí; mixed-mode kolony; dvourozměrná kapalinová chromatografie